Ação sinergística de celulases e hemicelulases fúngicas na hidrólise do bagaço de cana-de-açúcar após pré-tratamento alcalino - Rodrigues, Patrisia de Oliveira (2016)
Enzymatic hydrolysis of lignocellulosic wastes using microbial enzymes has been the target of research in Brazil and in the world with the aim to obtain high yields in fermentable sugars. In this work, the synergistic efficiency of crude enzymatic extracts produced by Aspergillus fumigatus (SCBM6) and Aspergillus niger (SCBM1) fungal strains was evaluated in the hydrolysis of sugarcane bagasse previously subjected to alkaline pre-treatment. Extracts produced by Solid State fermentation (SSF) showed high concentrations of three major enzymes in saccharification processes of lignocellulosic biomass: β-glucosidase (SCBM6 strain with 78.47 U/g and SCBM1 with 73.0 U/g), β-xylosidase (produced only by SCBM1 strain: 78.0 U/g) and xylanase (SCBM6 and SCBM1 with 1774.50 and 3289.58 U/g, respectively). The alkaline pretreatment of sugarcane bagasse with 2% sodium hydroxide was successful in the lignin removal, with a reduction from 26.14 at in natura bagasse (BB) to 14.9% in treated bagasse (BT), in the preservation of the cellulose fraction (from 54.36% in BB to 75.04% in BT) and in the increased porosity of the fibers. The pretreated sugarcane bagasse (BT) was submitted to 30 different conditions of hydrolysis using crude enzymatic extracts produced by A. fumigatus SCBM6 (designated EAF) and A. niger SCBM1 (EAN). The hydrolysis conditions were delineated by Surface Response methodology, varying the time, temperature, substrate concentration and ratio of extracts in the enzymatic cocktails. The maximum yield (28.66%) of total reducing sugars (TRS) was obtained after hydrolysis carried out during 12 hours, at 47°C, with 1U/g of β-glucosidase of each extract, 2.2% bagasse and ratio of EAN/EAF extracts of 25/75%. The quantification of the released monossacharides showed 135.59 mg xylose / g hemicellulose, 58.01 mg arabinose / g hemicellulose and 20.18 mg glucose / g cellulose. After hydrolysis using concentrated enzymatic extracts (10U/g of β-glucosidase of each extract), the concentration of the released pentoses increased considerably (xylose 694.45 mg/g and arabinose 4715.01 mg/g hemicellulose).